INTERNATIONAL INVESTMENT LAW WITHIN THE SYSTEM OF INTERNATIONAL LAW - D. K. LABIN; A. V. SOLOVYEVA (Московский журнал международного права, 2018)
INTRODUCTION. This article is aimed at reducing the gap between Russian and Western schools of international investment law, and offers an opportunity to gain adequate understanding of the proper place of international investment law within the system of international law. So far there has been no recognised attempt to complete a research which would analyse both approaches in order to make a comparison between conceptual discrepancies of the two doctrines first-hand based on an analytical product.MATERIALS AND METHODS. The authors undertake to research and analyse the most recent academic literature. As a result, this article includes references to both Russian and Western works in the field of international investment law published over the past ten years. However, there are occasional references to the classic academic contributions which have certainly proven their lifetime doctrinal value. As for the methodology, the authors opt to employ popular scientific research methods (including dialectics, analysis and synthesis, deduction and induction, comparative legal and historical analysis).RESEARCH RESULTS. As a result of the conducted research the authors offer a comprehensive overview of the doctrinal positions of Russian and Westerns academics which can be found in Russian and Western academic law literature. The authors summarise approaches and make conclusions about similarities and discrepancies between Russian and Western doctrines of international investment law.Discussion and conclusions. In this article the authors underscore a critical distinction in the interpretation of international investment law as a field of private international law (advocated by Russian doctrine) and as a field of international law (supported by Western doctrine). The article reveals the challenge in finding a proper definition for international investment law as a standalone law concept. Based on the findings the authors make an attempt to put forward a compromising approach to the place of international investment law within international law.